Introduction to special section: Why marketing still matters in Oceania and Asia - Phau, Ian; Garrett, T. (Elsevier, 2018)
© 2018 Cultural diversity is the norm in today's society, and past research has shown that ethnic cues in advertisements are effective in targeting ethnic consumers. This study extends this research stream by examining how ethnic identify impacts ethnic consumers’ perceptions of advertising in ethnic versus mainstream newspapers. The results show that ethnic consumers with higher ethnic identity have more positive responses towards advertisements with ethnic cues, particularly when the advertisements appear in ethnic newspapers. By contrast, for the same advertisements, mainstream media appears less effective in eliciting positive responses. Ethnic consumers with higher ethnic identity are also more likely to purchase and recommend products advertised in ethnic media. These findings offer insights to marketers and businesses who are targeting ethnic consumers. They shed light on when and how to use ethnic cues, particularly in ethnic media, in order to achieve desirable marketing and communication strategies that target ethnic consumers.